2000
DOI: 10.1128/aem.66.11.4615-4619.2000
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antibiotic Resistance of Bacteria Isolated from Larvae of the Oil Fly, Helaeomyia petrolei

Abstract: Helaeomyia petrolei (oil fly) larvae inhabit the asphalt seeps of Rancho La Brea in Los Angeles, Calif. The culturable microbial gut contents of larvae collected from the viscous oil were recently examined, and the majority (9 of 14) of the strains were identified as Providencia spp. Subsequently, 12 of the bacterial strains isolated were tested for their resistance or sensitivity to 23 commonly used antibiotics. All nine strains classified as Providencia rettgeri exhibited dramatic resistance to tetracycline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…Antibiotic-resistant enterococci were also isolated from stored-product beetles collected from a feed mill, a grain storage silo, and a retail store (37). A few other studies showed that Mexican fruit flies (Anastrepha ludens L.) from laboratory-reared colonies (38), oil fly (Helaeomyia petrolei L.) larvae from asphalt seeps (39), and cockroaches (Periplaneta americana L. and Blattella germanica L.) from food-handling facilities, households, and a hospital (40,41) are carriers of antibiotic resistance traits.…”
Section: Antibiotic Resistance and Insectsmentioning
confidence: 99%
“…Antibiotic-resistant enterococci were also isolated from stored-product beetles collected from a feed mill, a grain storage silo, and a retail store (37). A few other studies showed that Mexican fruit flies (Anastrepha ludens L.) from laboratory-reared colonies (38), oil fly (Helaeomyia petrolei L.) larvae from asphalt seeps (39), and cockroaches (Periplaneta americana L. and Blattella germanica L.) from food-handling facilities, households, and a hospital (40,41) are carriers of antibiotic resistance traits.…”
Section: Antibiotic Resistance and Insectsmentioning
confidence: 99%
“…We used PMB as a representative of this class of molecule for evaluating the resistance levels of different strains of Y. pestis to CAMP. While the actual relatedness of PMB to insect CAMPs is not entirely clear, it has been shown that representatives of both pathogenic and symbiotic bacteria isolated from insects are resistant to PMB (11,23,29), suggesting PMB has a spectrum of activity similar to that of insect CAMPs. Secondly, though insect CAMPs are rather heterogeneous in their structures and mechanisms of action, some insect immune peptides, such as the cecropins, have a spectrum of antibacterial activity similar to that of PMB (14).…”
Section: Vol 73 2005 Y Pestis Susceptibilities To Serum and Polymymentioning
confidence: 99%
“…Since it is difficult to imagine that these compounds cross the OM by a unique, unconventional route, this result, if confirmed, may indicate that the major pump discriminates between these substrates. Isolates of P. rettgeri from larvae of the oil fly have shown a correlation between natural resistance to a variety of antimicrobials and organic solvent tolerance, a phenomenon indicating strong efflux involvement (314).…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%